Human Resource Management, Organizational Commitment and Organizational Performance: Development, Test and Correction of Tthe Causal Model - Nasiri, Shahram (International Review of Management and Marketing, 2017)
The evaluation of organizational performance and its related impacts is regarded as one of the discussed factors. The most important factors in the development of organization, is the correct efficiency of the human resources in the organization. In order to promote the performance of the organization, the performance of the organizational resources should managed and controlled. The organizational commitment is one of the fundamental concepts in the human resource management resulting in the increased performance. The employee’s commitment in the organization should be in such a way that the individuals are willing to attend into the organization so that the organization can achieve a level of successfulness. The organizational commitment cause to promote and increase the productivity of the organizational performance. The present study aimed to analyze the relationship between human resource management, organizational commitment and the organizational performance of the employees in education Bureau in Sirjan. This is descriptive correlational study which uses self-made questionnaire for data collection. The statistical population consists of 65 employee of the education Bureau in Sirjan city. Data analysis was conducted using correlation test, path analysis, and structural equation model using software R. The finding of the study revealed that there is a poor and medium relationship between the human resource management and organizational commitment and the organizational performance of the employee. In addition, there was a medium relationship between the organizational commitment and organizational performance of the employee. Moreover, it is observed that there is a strong relationship between the research hypotheses. The results of the study suggested that the education Bureau should attempt to manage their human resource and the increased responsibility as well as working independence so that it can have a significant impact on the increased commitment of the education Bureau and the improved performance of the organization. Keywords: Human resource management, organizational commitment, organizational performance. JEL Classifications: L2, O15